Epidermal growth factor modulates prostate cancer cell invasiveness regulating urokinase-type plasminogen activator activity - Festuccia, Claudio; Angelucci, Adriano; Gravina, Giovanni Luca; Biordi, Leda; Millimaggi, Danilo; Muzi, Paola; Vicentini, Carlo; Bologna, Mauro (Thrombosis and Haemostasis, 2005)
Urokinase-type plasminogen activator receptor (uPAR) and Epidermal Growth Factor Receptor (EGFR) are ubiquitous receptors involved in the control of a variety of cellular processes frequently found altered in cancer cells. The EGFR has been recently described to play a transduction role of uPAR stimuli, mediating uPA-induced proliferation in highly malignant cells that overexpress uPAR. We compared the uPA production, the presence of uPAR, AR, EGFR and Her2 with the chemotaxis and the Matrigel invasion in ten human PCa cell lines and observed that: (1) the levels of Her2, but not of EGFR, as well as the uPA secretion, cell motility and Matrigel invasion were statistically higher in AR negative than in AR positive PCa cells; (2) the uPA secretion and uPAR expression were positively related to Matri-gel invasion; (3) the EGF was able to stimulate chemotaxis and Matrigel invasion in a dose-dependent manner; (4) the EGF-induced cell migration was statistically higher in AR negative than in AR positive cells with a similar increase with respect to basal value (about 2.6 fold); (5) the Matrigel invasion was statistically higher in AR negative than in AR positive PCa cells also if the increment of Matrigel invasion after EGF treatment was statis- tically higher in AR positive respect to AR negative cells; (6) the EGF induced uPA secretion and its membrane uptake through the increment of uPAR; and (7) these effects were blocked by EGFR/Her2 tyrosine kinase inhibitors with IC50 lower than those needed to inhibit cell proliferation and required PI3K/Akt, MAPK and PI-PLC activities as verified by inhibition experiments. These enzymatic activities were regulated in different manners in PTEN positive and negative cells. In fact, the inhibition of PI3K blocked the EGF-induced invasiveness in PTEN positive cells but not in PTEN negative cells, in which PI3K activity was not influenced by EGFR/Her2 activation, whereas the inhibition of MAPK was able to block the invasive phenomena in both cell types. Taken together, our data suggest that the blockade of EGFR could attenuate the invasive potential of PCa cells. In addition, considering that the EGFR expression is related to higher Gleason grade of PCa and that EGFR levels are increased after anti androgenic therapy, this therapeutic approach could slow down the metastasis formation which represents the most dramatic event of PCa progression.
Keywords: Prostatic carcinoma; EGFR; uPA; tyrosine kinase inhibitors